Hematological Risk Factors for High-Altitude Headache in Chinese Men Following Acute Exposure at 3,700 m - Huang, He; Liu, Bao; Wu, Gang; Xu, Gang; Sun, Bing-Da; Gao, Yu-Qi (Frontiers in Physiology, 2017)
Background: High-altitude headache (HAH) is a notably common disorder affecting the daily life of travelers ascending to high altitude. Hematological parameters are important clinical examinations for various diseases. Today, hematological characteristics of HAH remain unrevealed. Above all, we aimed to ascertain hematological characteristics and independent risk factors/predictors associated with HAH before and after exposure at 3,700 m. Methods: 45 healthy men were enrolled in present study. Demographic and clinical data, physiological and hematological parameters were collected three days before the ascent and after acute exposure at 3,700 m. Results: HAH patients featured significantly lower white blood cell count (WBC), neutrophil count (NEU#) and percentage (NEU%), and higher percentage of lymphocyte (LYM%) at 3,700 m and significantly lower NEU#, reticulocyte count (RET#) and percentage (RET%) at sea level (all P < 0.05). HAH severity was significantly and negatively associated with WBC, NEU#, and NEU% at 3,700 m and RET# at sea level, whereas was positively associated with LYM% at 3,700 m (all P < 0.05). Moreover, we have found that RET# at sea level and NEU% at 3,700 m was an independent predictor and risk factor for HAH, respectively. Conclusion: The present study is the first to examine the hematological characteristics of HAH. Furthermore, lower RET# at sea level and lower NEU% at 3,700 m is a novel independent predictor and risk factor for HAH, respectively.